Egy szétszakított térség újraintegrálódásának kezdete: határnyitás az osztrák-magyar határon - Tóth, Imre (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In 1988-1989 a stream of East Germans sought refugee in Hungary at the Embassy of West Germany in Budapest. The three countries taking part in the issue made different solutions to deal with the increasing problem. The East German leadership tried to call back the refugees and calm down the emigration process, but it had lost its confidence. West Germany tried to solve the problem not only on the level of consulship but exten-sively, in part with recognizing the status those waiting for West German citizenship and those for refugee status - without any success. In the interest of the resolution and bring the Hungarian leadership to their point of view, they tried to make use of the international organizations. However, the Hungarian leadership made efforts to stay out of the issue to get the two German states make an agreement. But there was no chance for that so Buda-pest gave up its quasi neutrality and tried to solve the problem opening the border by avoiding Hungary to turn into a refugee camp of the region. Besides making this ad hoc arrangement, the whole issue needed more radical crisis management, not only in Hungary.